Immunological changes with kinase inhibitor therapy for chronic lymphocytic leukemia. Issue 12 (2nd December 2018) - Pleyer, Christopher; Wiestner, Adrian; Sun, Clare
Abstract: Ibrutinib and idelalisib are kinase inhibitors that have revolutionized the treatment of chronic lymphocytic leukemia (CLL). Capable of inducing durable remissions, these agents also modulate the immune system. Both ibrutinib and idelalisib abrogate the tumor-supporting microenvironment by disrupting cell–cell interactions, modulating the T-cell compartment, and altering the cytokine milieu. Ibrutinib also partially restores T-cell and myeloid defects associated with CLL. In contrast, immune-related adverse effects, including pneumonitis, colitis, hepatotoxicity, and infections are of particular concern with idelalisib. While opportunistic infections and viral reactivations occur with both ibrutinib and idelalisib, these complications are less common and less severe with ibrutinib, especially when used as monotherapy without additional immunosuppressive agents. This review discusses the impact of ibrutinib and idelalisib on the immune system, including infectious and auto-immune complications as well as their specific effects on the B-cell, T-cell, and myeloid compartment.